OTONOMI KULTURAL SEKOLAH STUDI KASUS PADA SD NEGERI DI BANDUNG - Oong Komar (Universitas Negeri Yogyakarta, 2004)
Abstract The purpose of this study is to describe the elementary school culture autonomy. This is a qualitative research. The information is collected by observation, interview, questionnaire and documentation, and then analyzed through finding formulation stage, member check, and experts’ feedback. It was found that school culture autonomy arouse personnel potency to improve the routine, boring, obsessive, and less productive behavior continuously. In addition it increased critical climate, such as personnel behavior in accepting his supervisor or bureaucrat instruction and in facing pupil parents’ demand. Keywords: autonomy, culture autonomy, elementary school